Epidemic Keratoconjunctivitis: A Growing Concern in Pakistan - Nafia Hijab; Fariya Majid; Khushboo Nusrat; admin (Journal of the Pakistan Medical Association, 2024)
Dear Editor, A significant public health concern in Pakistan has arisen—a concerning surge in cases of Epidemic Keratoconjunctivitis (EKC). Though a relatively mild ocular disease, this form of viral conjunctivitis primarily attributed to adenoviruses is being widely reported in Pakistan, highlighting its rapid transmission potential. EKC, characterized by marked conjunctival inflammation, photophobia, pain, lymphadenopathy and occasional vision impairment, stands out for its remarkable ability to spread swiftly.1 This inherent transmission risk makes EKC a critical matter to address in our densely populated communities. While EKC is typically a self-limiting condition with a relatively low risk of severe complications, corneal involvement poses a concern. Within the first week of adenoviral conjunctivitis, individuals may experience the onset of punctate or geographic epithelial keratitis. This early development can serve as an indicator for the later occurrence of stromal keratitis. It presents as the formation of subepithelial infiltrates, which frequently endure or reappear for extended periods, even after the acute infection has cleared.2 The economic implications of EKC are of concern, especially for individuals facing financial adversity. Medical expenses, the cost of pharmacological interventions, and the absence from work can strain an individual’s financial condition.3 Our healthcare infrastructure, already facing multiple challenges, experiences added pressure as EKC cases rise. Though EKC does not often require intensive medical care, the speedy transmission and sheer number of cases can strain our clinics and limited healthcare resources, underscoring the urgency of a proactive response. Prevention and education remain our best defences against EKC. We must vigorously promote hand hygiene, advocate for minimizing close ocular contact, and emphasize timely medical attention.1 Adequate disinfection, especially of medical instruments, proves to be essential in combatting the spread of infection, even more so than washing of hands.4,5 Maintaining proper hygiene is a crucial strategy as it has been demonstrated to substantially decrease the duration of the epidemic outbreak.6 In conclusion, it is paramount that we recognize and address the transmission risks associated with Epidemic Keratoconjunctivitis, particularly within the context of Pakistan’s densely populated areas. I urge healthcare authorities, professionals, and the media to unite in disseminating critical information and advocating for preventive measures. By doing so, we can effectively mitigate the spread of EKC while ensuring our healthcare system remains resilient.